201k views
0 votes
Solve using the quadratic formula x2+3x-3=0

User Vivkv
by
6.2k points

2 Answers

5 votes

Answer:

x=(-3+-sqrt15)/2

Explanation:

Without using calculatorsoup,

we can use the quadratic formula for x^2+3x-3=0

using it we find:

x=(-b+-sqrtb^2-4ac)/2a

x=(-3+-sqrt3-4*1*-3)/2

x=(-3+-sqrt15)/2

User Paulo Roberto Rosa
by
6.1k points
4 votes

For this case we must resolve the following expression:


x ^ 2 + 3x-3 = 0

The roots will be given by:


x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}

We have to:


a = 1\\\b = 3\\c = -3

So:


x = \frac {-3 \pm \sqrt {3 ^ 2-4 (1) (- 3)}} {2 (1)}\\x = \frac {-3 \pm \sqrt {9 + 12}} {2}\\x = \frac {-3 \pm \sqrt {21}} {2}

We have two roots:


x_ {1} = \frac {-3+ \sqrt {21}} {2} = 0.7913\\x_ {2} = \frac {-3- \sqrt {21}} {2} = - 3.7913

Answer:


x_ {1} = \frac {-3+ \sqrt {21}} {2} = 0.7913\\x_ {2} = \frac {-3- \sqrt {21}} {2} = - 3.7913

User MateodelNorte
by
5.5k points